Formation of Cardiointervalograms Based on Photoplethysmographic Realizations of Peripheral Pulse Signals - О. В. Гусєва; В. С. Мосійчук; О. Б. Шарпан (Vìsnik Nacìonalʹnogo Tehnìčnogo Unìversitetu Ukraïni Kììvsʹkij Polìtehnìčnij Ìnstitut: Serìâ Radìotehnìka, Radìoaparatobuduvannâ, 2023)
Features and possibilities of implementation of heart rate variability (HRV) cardiosystems based on the registration of peripheral photoplethysmographic pulse signals, which are easier and more convenient to register than electrocardiogram signals, are considered. The possibility of assessing the functional state using both long and short implementations of pulse signals without loss of accuracy in determining the diagnostic significance of statistical and spectral HRV parameters is indicated. The expediency of assessing heart rate variability not only by the parameters of one pulse signal registered at a certain point of the body, but also by the parameters of several such signals registered at different points of the human body, for example on the limbs, with an assessment of the differences in heart rate variability relative to the sagittal plane, is shown.